Development of Fishburgers From Selaroides Leptolepis, Aristichthys Nobilis and Alutera Monoceros - Siah, Watt Moey (1997)
Selaroides leptolepis, Aristichthys llobilis and Alutera monoceros were used to develop frozen fish product aimed at fast food outlets and households. At the idea generation stage, 24 product ideas were generated. The 24 product ideas were reduced to three using a series of scoring techniques for screening. Fishburgers were chosen for furthur development. The formulation for fishburger was established using a sensory panel A final consumer testing of the product was carried out in a nearby housing area. A sample size of 60 households was used. Results showed that the market potential for this product is expected to be very good as 75% of the respondents are willing to buy this product if it is in the market. The acceptable price range is RM 5.50 to RM 6.50. Fishburgers packed in LDPE bags, PP semi rigid containers and PS tray over wrapped with LDPE cling flim were acceptable after 18 weeks of storage at -20°C. The storage quality in terms of thiobarbituric acid no (TBA), trimethylamine (TMA) and total volatile basic nitrogen (TVBN) showed significant (P<0.05) increases. There were decreases in salt soluble protein, pH, moisture content and microbial counts. Fishburgers in PP semi rigid containers had the best stability followed by samples in LDPE bags and PS + LDPE. The effects of washing and storage on the quality of S.leptolepis and A. nobilis surimi kept at -20°C for 24 weeks were studied. Surimi was prepared from unwashed, once-washed and twice-washed minces. The storage quality in terms of texture, colour, elasticity, moisture content, pH and SSP values for all samples showed significant (P<0.05) decreases during storage. There were increases in expressible moisture, TMA, TVBN and TBA. Results also showed that twice-washed mince of both species were generally more stable than once-washed and unwashed minces.